2022
DOI: 10.3390/biomedicines10061393
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Serum Albumin Ratio: A Feasible Prognostic Marker in Hospitalized Patients with COVID-19

Abstract: (1) Background: C-reactive protein (CRP) and albumin are inflammatory markers. We analyzed the prognostic capacity of serum albumin (SA) and CRP for an outcome comprising mortality, length of stay, ICU admission, and non-invasive mechanical ventilation in hospitalized COVID-19 patients. (2) Methods: We conducted a retrospective cohort study based on the Spanish national SEMI-COVID-19 Registry. Two multivariate logistic models were adjusted for SA, CRP, and their combination. Training and testing samples were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Larger prospective cohort studies with subgroup analysis by risk subgroups is essential to validate the findings of this study. Despite the lack of novelty in identifying the severity prediction values of the biomarkers studied here, the results confirmed the results of previous studies [9,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Larger prospective cohort studies with subgroup analysis by risk subgroups is essential to validate the findings of this study. Despite the lack of novelty in identifying the severity prediction values of the biomarkers studied here, the results confirmed the results of previous studies [9,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Sarkar et al [ 20 ] evaluated the role of PLR in COVID-19 patients upon admission (14 studies; 2768 patients) for mortality, showing a WMD of 66.10 (95% CI: 47.75–84.44) with high heterogeneity (I2 = 89%) and low-quality evidence; a meta-analysis of 71 studies found no association for PLR with a poor prognosis in terms of mortality [ 21 ]. Moreover, a retrospective study evaluated the role of the CRP to serum albumin ratio in 272 COVID-19 patients in terms of mortality, finding an optimal cut-off above 21.5 (c-statistic of 0.72; 95% CI 0.66–0.77) [ 22 ], whereas another study that involved 3471 patients showed an optimal cut-off above 25 to be associated with mortality (OR, 1.47; 95% CI 1.19–1.82) [ 23 ]. A meta-analysis conducted by Zavalaga-Zegarra et al [ 24 ] evaluated the potential association of the CPR to albumin ratio in terms of mortality in 17 studies (7164 COVID-19 patients), finding higher values in non-survivors (MD: 2.59; 95% CI: 1.95–3.23) with severe heterogeneity (I2 = 92%).…”
Section: Discussionmentioning
confidence: 99%
“…The study population we included had different severities of illness, and the overall mortality rate was 19%. Many studies have used various biomarkers, such as CRP [39][40][41][42][43][44], PCT [39,43,45,46], IL-6 [39,43,46], WBC [40,[47][48][49], D-dimer [42,44,46,50,51], lactate dehydrogenase (LDH) [39,[42][43][44]46,47], N-terminal pro-B-type natriuretic peptide (NT-proBNP) [39,52,53], and Troponin T [39,54], and critical illness score, such as APACHEII [55][56][57], SOFA [55,56,[58][59][60], SAPS [61-64], and CURB65 [59,61,65], to evaluate the prognosis of patients with COVID-19. The APACHE II and SOFA scoring systems require the worst values of the clinical and biological parameters to be recorded within 24 h of admission [66].…”
Section: Discussionmentioning
confidence: 99%